Adoption of Biosimilar Infliximab for Rheumatoid Arthritis, Ankylosing Spondylitis, and Inflammatory Bowel Diseases in the EU5: A Budget Impact Analysis Using a Delphi Panel - Kanters, Tim A.; Stevanovic, Jelena; Huys, Isabelle; Vulto, Arnold G.; Simoens, Steven (Frontiers in Pharmacology, 2017)
Introduction. Introducing biosimilar infliximab for the treatment in rheumatology (rheumatoid arthritis and ankylosing spondylitis) and inflammatory bowel disease (Crohn’s disease and ulcerative colitis) may reduce treatment costs associated with biologics. This study aimed to investigate the budget impact of adopting biosimilar infliximab in five European countries, considering that the budget impact includes the adoption of biosimilar infliximab and the availability of biologic alternatives such as vedolizumab, biosimilar etanercept, biosimilar rituximab and other relevant factors. Methods. An existing budget impact model was adapted to forecast the budget impact in the UK, Germany, France, Spain and Italy. Epidemiological parameters were derived from published literature reviewed in July 2015. Current market shares of biologics were derived from Therapy Watch (2012/2013 data). Respondents in a Delphi panel, conducted in 2015 and consisting of several leading rheumatologists and gastroenterologists from different nationalities, were asked to forecast uptake of biosimilar infliximab and estimate the proportion of patients eligible for a particular type of biological treatment, including biosimilar infliximab. Scenario analyses assessed the influence of various factors on the budget. Results. Uptake of biosimilar infliximab was particularly expected for naïve patients; switching patients that already received other biologics was not expected much. Market shares after five years of biosimilar infliximab were approximately 2% in rheumatology in all five countries and in gastroenterology ranged from 4% in France to over 30% in Italy. Except for France, budgets were expected to decrease for rheumatologic diseases. For gastroenterology, budgets were expected to decrease in Spain and Italy. Budgets were expected to increase substantially in the UK and Germany, due to the introduction of vedolizumab in the studied period. In France, budget was expected to slightly increase for ankylosing spondylitis, Crohn’s Disease and ulcerative collitis. Savings in budget were expected in all countries, for all diseases, when larger price discounts on biosimilar infliximab were used. Discussion and conclusion. This study has shown that only when price reductions are large enough (i.e. 50% or more), physicians indicated that they will prescribe biosimilars. Policy makers should ensure substantial price reductions and stimulate physicians to use biosimilar products, to obtain savings in healthcare budgets.